Movement-Versus Sporting-Based Physical Education in Elementary Schools: Does Either Ensure Quality? - Scott, Joseph John (Universitas Pendidikan Indonesia, 2019)
Within the physical education literature, there remains to be contentions between the effectiveness of sporting- and movement-based approaches. Whilst both have noted strengths and weaknesses, there is little research into whether either is leading to quality physical education in Australian elementary schools. This paper therefore examines two of the common models based approaches to teaching physical education in elementary schools against the five interrelated propositions of the Australian Curriculum to determine if either pedagogical approach is leading to quality physical education. This paper draws on current literature, curriculum frameworks and pedagogical recommendations to determine the value of a models based approaches to physical education in relation to quality. Examinations indicate that both the sports and movement based approaches can address the five key propositions that underpin the Australian Curriculum, however quality is dependent on appropriate implementation by qualified and skilled teachers. Teacher education and pedagogical knowledge is paramount for the implementation of quality physical education. Further investigation and exploratory research is required to determine if the model based approaches are being effectively being introduced by both generalist and specialist health and physical education teachers in elementary school settings.